Aventura espacial: um jogo sério de interface adaptativa voltado a crianças e jovens com transtorno do espectro do autismo - Rodrigues, Rafael de Almeida (Universidade Federal Rural do Semi-Árido, 2019)
Autism spectrum disorder is characterized by persistent deficits in the ability to initiate and sustain reciprocal social interaction and social communication. The study of this disorder makes it possible to carry out research that helps in the treatment through the use of information and communication technologies. In this context, it is proposed the development of a serious game of adaptive interface for children and young people with autism spectrum disorder. Through the profile of users and their experiences as they play, the interface and challenges change. The conditions that determine the adaptations in the game were constructed with different written records: logbooks written during workshops held in mental health environments by students in a direct interaction with users; written analyzes of perceived recurrences in game situations and interviews with experts who follow weekly workshops at CAPSi. We try to define the best techniques and methods to reach the objectives in the accomplishment of the game Aventura Espacial. The purpose of the present research is the production of a game that invites the user to experience social interaction with others and the circumstances of the environment in which it is inserted. In the validation work we could see that the experience of the young people in the game encourages the different ways of functioning of the attention with the challenges and suggestions that the game offers. The game Aventura Espacial enables the mental health professional to follow the course of their achievement by each user.
Keywords: Transtorno do Espectro Autista; Jogo Sério; Cognição; Interação; Saúde Mental; Autism Spectrum Disorder; Serious Game; Cognition; Interaction; Mental Health; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO